Substantive evidence of initial habitation in the remote Pacific : archaeological discoveries at Unai Bapot in Saipan, Mariana Islands - Carson, Mike T., (Archaeopress Publishing Ltd, 2017)
At the Unai Bapot Site of the Mariana Islands, new excavation has clarified the oldest known instance of a residential habitation prior to 1500 B.C. in the Remote Pacific, previously difficult to document in deeply buried layers that originally had comprised near-tidal to shallow subtidal zones.